Treatment of Tactile Impairment in Young Children with Autism: Results with Qigong Massage - Silva, MD, MPH, Louisa; Schalock, BSc, Mark (International Journal of Therapeutic Massage & Bodywork, 2013)
Background: Following the inclusion of sensory abnormalities in the diagnostic criteria for autism, evidence has emerged showing that tactile abnormalities in young children with autism are severe, universally present, and directly related to delay of early self-regulation milestones required for social development. Parent touch is the most effective means of stimulating early self-regulation, yet parents of children with autism avoid touch because their children respond abnormally to it. This suggests that tactile abnormalities pose a barrier to parent touch in autism, and that treatment of tactile abnormalities may improve developmental outcomes. We have developed a qigong massage treatment for tactile abnormalities in young children with autism. Here we evaluate whether tactile abnormalities decrease following treatment, and whether treatment results in improved selfregulatory outcomes.Methods: We retrospectively analyzed our qigong massage database for treatment effect on tactile abnormalities, self-regulatory delay, and parenting stress. Five-month interval data were available for 129 children with autism aged 3–6 years. Of these 129, 97 received treatment and 32 were in the wait-list control condition. There were no differences between treatment and control groups by age, gender, or severity of tactile impairment.Results: Treatment resulted in significant decreases of tactile impairment, self-regulatory delay, and parenting stress (p < .001 on all paired t-tests); mean decreases were 25.5%, 24.5%, and 35.8%, respectively. Results were significant compared to controls [F(3,122) = 11.27, p < .001]. In the pretreatment data, tactile impairment was directly related to self-regulatory delay; post-treatment, both variables decreased proportionally.Conclusion: Results demonstrate that tactile impairment in young children with autism is treatable with a qigong massage protocol. The direct relationship between tactile impairment and self-regulatory delay pretreatment, and the proportional decrease of both following treatment, suggest that tactile impairment is a cause of self-regulatory delay, and that qigong massage is a promising avenue to improve developmental outcomes in autism.